Differentiation-dependent human immunodeficiency virus long terminal repeat regulatory elements active in human teratocarcinoma cells. - Zeichner, S L (1992)
We have examined the transcriptional utilization of the human immunodeficiency virus type 1 (HIV-1) long terminal repeat (LTR) under differentiating conditions by using the embryonal carcinoma cell line NTERA-2. NTERA-2 cells undergo two distinct pathways of terminal differentiation, to a neuronal phenotype in response to retinoic acid and to a nonneuronal phenotype in response to hexamethylene bisacetamide. To identify LTR regulatory elements active in each cell type we used a set of HIV LTR linker substitution mutants, which contain mutations that progressively replace adjacent 18-bp segments across the U3 region and into the R region (between nucleotides -453 and +15 relative to the transcription start site). Although each differentiating cell type showed utilization of expected key elements (e.g., NF-kappa B, SP1, TATA) in the 3' portion of the LTR (+1 to -112), the data indicated differentiation-dependent differences in the utilization of these elements. In addition, regions showing dramatic differentiation-dependent effects were detected in the 5' portion of the LTR (-112 to -453), in positions where transcription control elements have not been described previously. The marked differences in the sets of LTR regulatory elements required by each cell type indicate that the LTR can function under a variety of differentiation conditions. Together with previous findings, the data suggest that the complexity of the HIV LTR for transcriptional control is much greater than was previously thought and that the LTR maintains elements which facilitate transcription in many cell types.